Correlation between NK function and response to trastuzumab in metastatic breast cancer patients - Spadi Rosella; Polimeni Maria; Mistrangelo Marinella; Brusa Davide; Evangelista Andrea; Signorino Elena; Beano Alessandra; Donadio Michela; Ciuffreda Libero; Matera Lina (Journal of Translational Medicine, 2008)
Abstract Background Trastuzumab is a monoclonal antibody selectively directed against Her2 and approved for the treatment of Her2 overexpressing breast cancer patients. Its proposed mechanisms of action include mediation of antibody-dependent cellular cytotoxicity (ADCC) by triggering FcγRIII on natural killer (NK) cells. This study addresses the correlation between overall NK function and trastuzumab's clinical activity. Subjects and methods Clinical and immunological responses were assessed in 26 patients receiving trastuzumab monotherapy as maintenance management after chemotherapy (8 mg/kg load and then standard doses of 6 mg/kg every 3 weeks). Cytotoxic activity against the MHC class I-negative standard NK target K562 cell line and HER2-specific ADCC against a trastuzumab-coated Her2-positive SKBR3 cell line were assessed in peripheral blood mononuclear cells (PBMC) harvested after the first standard dose. After six months, seventeen patients were scored as responders and nine as non-responders according to the RECIST criteria, while Progression-Free Survival (PFS) was calculated during a 12 months follow-up. Results The responders had significantly higher levels of both NK and ADCC activities (p < 0.05) that were not different from those of eleven normal controls. The NK activity of the non-responders was significantly (p < 0.05) lower than that of the normal controls. At twelve months, there was a marked correlation between PFS and NK activity only. PFS was significantly longer in patients with high levels of NK activity, whereas its pattern was unrelated to high or low ADCC activity. Conclusion One of the mechanisms of action of trastuzumab is NK cell-mediated ADCC lysis of the Her2-positve target cell. We show here that its potency is correlated with the short-term response to treatment, whereas longer protection against tumor expansion seems to be mediated by pure NK activity.